NOT ONLY VITAMIN D BUT HAEMOGLOBIN IS ALSO ASSOCIATED WITH ARM FRACTURES IN PAEDIATRIC PATIENTS!! - Dr Suchi Acharya; Dr Achinta Mallick; Dr Kumar Pushkar; Dr Manish Kumar; Dr Manish Kumar (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Introduction: Vitamin D deficiency usually linked with skeletal complications includes rickets, bone deformities, osteoporosis and fractures. The aim of the present study was to determine the prevalence of vitamin D deficiency in under 6 years paediatric patients presented with radiographically conﬁrmed fracture of upper arm extremity.Material and methodsThis cross-sectional descriptive study was conducted at a tertiary care centre in western Maharashtra between Jan 2019 to Dec 2021. All pediatric patients under 6 years with radiographically conﬁrmed fracture of upper extremity during the study period were compared with collected serum levels of 25(OH) vitamin D and haemoglobin by using an electronic statistical package SPSS software version 23.0 (SPSS, IBM, Chicago, IL, USA).ResultsA total of 62 children were enrolled in the study. In our study, almost three fourth (47, 75.8%) of children with upper extremity fracture were deficient (< 20ng/ml) in serum levels of 25(OH) vitamin D.  The statistical comparison of median serum haemoglobin level and mode of injury by using Mann Whitney U test was significant, p-value = 0.002  whereas, statistical comparison of median serum levels of 25(OH) vitamin D and mode of injury was found to be non-significant, p-value = 0.133.Conclusion We found almost 75% children in our study were suffering from Vit D deficiency. However, this study showed a potentially important association between low serum haemoglobin levels and fracture due to low impact injury in children. This finding opens-up a window of opportunity for research on the effect of haemoglobin and possibly nutritional status on bone health.